Effect of fast-skin body suit on propulsion in four strokes by using indirect measurement of active drag (IMAD) - Shahbazi-Moghaddam, M.; Shahbazi, M. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The effect of Fast- skin suit compared to conventional swimsuits on propulsion in four strokes in 16 female national-level swimmers was studied. The propulsion was estimated by Indirect Measurement of Active Drag (IMAD). IMAD is an estimate of the overall propulsive drag on a swimmer measured in conditions near maximal speed. Remarkable difference in propulsive force has been obtained for butterfly swim: 15%, while 5.2% was achieved for backstroke. Our findings also showed that Fast-skin effect is more important in breaststroke; 9.5% than in even front crawl; 7.9%. The method has also enabled us to find out the changes in mean velocities; 5.7% for butterfly and 1.8% for back crawl and for maximal velocities 16.5% for butterfly and 3.4% for back crawl.